2007
DOI: 10.1007/s10704-007-9106-1
|View full text |Cite
|
Sign up to set email alerts
|

Plastic loads of elbows with local wall thinning under in-plane bending

Abstract: Based on systematic three-dimensional (3-D), large strain FE limit analyses using elasticperfectly plastic materials, this paper quantifies the effect of local wall thinning on plastic behavior and TES (twice-elastic-slope) plastic loads for 90 • elbows under in-plane bending. The thinning geometry is assumed to be rectangular rather than circular, but the nonlinear geometry effect is fully considered. Results from systematic analyses lead to simple approximations for TES plastic loads, covering a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…We inferred that the increasing efflux proportion of radiotracers may be caused by the intracellular dissociation and exocytosis of 177 Lu-DOTA-PEG-CPNs. [17] As for cytotoxicity, we found that the nanocarrier caused no inhibition on the cell growth of 4T1 cell even at a high concentration of 200 μg/mL, suggesting that DOTA-PEG-CPNs possess good biocompatibility. Meanwhile, 177 Lu-DOTA-PEG-CPNs can dramatically inhibit the cell viability from 66.4 % to 17.5 %, in a dose-dependent manner (from 0.46 to 7.40 MBq/ mL), which is much more efficient than that of free 177 Lu (Figure 1f).…”
Section: Resultsmentioning
confidence: 88%
“…We inferred that the increasing efflux proportion of radiotracers may be caused by the intracellular dissociation and exocytosis of 177 Lu-DOTA-PEG-CPNs. [17] As for cytotoxicity, we found that the nanocarrier caused no inhibition on the cell growth of 4T1 cell even at a high concentration of 200 μg/mL, suggesting that DOTA-PEG-CPNs possess good biocompatibility. Meanwhile, 177 Lu-DOTA-PEG-CPNs can dramatically inhibit the cell viability from 66.4 % to 17.5 %, in a dose-dependent manner (from 0.46 to 7.40 MBq/ mL), which is much more efficient than that of free 177 Lu (Figure 1f).…”
Section: Resultsmentioning
confidence: 88%
“…Importantly, unlike liposomes, EVs could leave the organism via cytosolic emesis to reduce toxicity. 129,130 For instance, Ho and coworkers revealed the mechanism of dodecyl-PEG-AuNP cytosolic vomiting. Dodecyl-PEG-AuNP was composed of dodecyl-terminated polyethylene glycol-coated gold nps.…”
Section: Liposomes Versus Evs For Drug Deliverymentioning
confidence: 99%
“…These results were ascribed to a faster uptake of our material into cancer cells, which translates into a higher intracellular camptothecin concentration, underscoring the potential of a targeting-free approach for drug delivery to cancer. Indeed, impaired vesicular trafficking 61,62 and higher metabolic activity 63 are common traits of cancer cells, which lead to their higher proliferation rates compared to non-cancerous phenotypes. Both these processes contribute to a higher accumulation of nanoparticles inside cancer cells, and indeed the implication of these parameters on the efficacy and targeting of cancer therapeutics has been already exploited.…”
Section: Biomaterials Science Papermentioning
confidence: 99%